Mussel-Inspired Microgel Encapsulated NLRP3 Inhibitor as a Synergistic Strategy Against Dry Eye - Zha, Zhiwei; Chen, Qiumeng; Xiao, Decheng; Pan, Chengjie; Xu, Wei; Shen, Liangliang; Shen, Jianliang; Chen, Wei (Frontiers in Bioengineering and Biotechnology, 2022)
The inflammatory response mediated by oxidative stress is the main pathogenesis of dry eye, but clinical observations have shown that scavenging oxygen free radicals alone has limited therapeutic effect. Moreover, the unique anatomy and physiology of the ocular surface results in low bioavailability of drugs, and higher concentration was required to reach the desired efficacy, which, however, may bring systemic side effects. These problems pose a challenge, but the revelation of the ROS-NLRP3-IL-1β signaling axis opens up new possibilities. In this investigation, a NLRP3 inhibitor was successfully encapsulated in polydopamine microgels and used for dry eye treatment. It was demonstrated that the well-designed microgels exhibited good biocompatibility, prolonged drug retention time on the ocular surface, and effective inhibition of corneal epithelial damage and cell apoptosis. In addition, due to the synergistic effect, the NLRP3 inhibitor-loaded microgels could exert enhanced oxygen radical scavenging and inflammation inhibiting effects at lower dose than monotherapy. These findings suggest that polydopamine-based microgels have advantages as ocular surface drug delivery platforms and have promising applications in oxidative damage-related inflammatory diseases in synergy with anti-inflammatory drugs.